Linking Scientific Cognition and the Experience of Nature: On the Interferences of Religion and Science in the Writings and Life of Werner Heisenberg - Schaa, Elena (Journal of the Irish Society for the Academic Study of Religions, 2021)
Werner Heisenberg is one among several renowned modern physicists who engaged in discourses on the relationship between religion and science. While discursive and conceptual research on religion and science has largely focused on the boundary work between the social systems, cultural and aesthetical studies have shed light on their interferences. The focus on the interferences extends the research on religion in the life and writings of Heisenberg beyond his arguments and considers the aesthetic strategies of his writings along with his academic practices. This article shows how through the model of "interferences" more than just Heisenberg’s interpretation of the world add to the relationships of modern religion and physics. Firstly, I offer an overview of Heisenberg's biography to draw attention to the moments when he becomes a relevant figure in the modern history of religion and the historical sources accessible for textual analysis. Secondly, I introduce concepts developed in the framework of "European History of Religion" in order to demonstrate the religious tendencies and aesthetic ideologies in Heisenberg’s texts. Thirdly, I discuss narratology as a productive methodology to include the formal aspects of Heisenberg's writing into the analysis. Ultimately, I will use two examples to show the different interferences in Heisenberg's career and writings: the Romano Guardini prize speech and his romanticised narrative of the "founding moment" of quantum mechanics in 1925, published forty years later in his popular book Physics and Beyond (Der Teil und das Ganze).